Antimicrobial effect of buffered sodium citrate, alone or combined with sodium diacetate, on total aerobic count of ground beef stored at 39°F - Ceylan, E.; Marsden, James L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We studied the antimicrobial efficacy of buffered sodium citrate and a combination of buffered sodium citrate and sodium diacetate on natural aerobic microflora of ground beef stored at 39°F. For non-treated control and 1% buffered sodium citrate, total aerobic count gradually increased from 4.2 log colony forming units (CFU)/gram initially to 9.0 and 8.7 log CFU/gram, respectively, after 10 days. Both treatments reached the spoilage index number of 7.0 log CFU/gram after 5 days. A combination of 1% buffered sodium citrate and 0.1% sodium diacetate resulted in a total aerobic count of 5.9 log CFU/gram (below the spoilage index) after 10 days of storage at 39°F. Combined 1% buffered sodium citrate and 0.1% sodium diacetate suppressed growth of aerobes and increased the shelf life of ground beef stored at 39°F.
Keywords: Beef; Buffered sodium citrate; Sodium diacetate; Ground beef